Analisis Anteseden Pembagian Dividen Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Periode Laporan 2017 – 2021 - Agus Tamrin Reni; Wahyu Satriyo Wicaksono; Della Jane Wijaya; Febrian Hermawan; Robin; Yulfiswandi (Jayapangus Press, 2023)
Investors have hope in the distribution of dividends in a company that aims to improve its welfare. The attainment of the firm's profit also affects the dividend size; if the company makes a lot of money, it will also pay out a lot of dividends, and vice versa. This study aims to analyze the components consisting of human capital efficiency, structural capital efficiency. Employed capital efficiency, value-added intellectual coefficient, and return on assets as control variables on dividends. Methods of data analysis using partial correlation analysis. A total of 787 companies that have been listed on the IDX are the population in this study. Based on the results of the research data analysis, it shows that 1) human capital efficiency has no effect on dividends with the control variable return on assets with a significance value of 0.909 > 0.05, 2) structural capital efficiency has an effect on dividends with the control variable return on assets with an acquisition value of significance of 0.029<0.05, 3) capital employed efficiency has no effect on dividends with the control variable return on assets with a significance value of 0.745>0.05, and 4) value added intellectual coefficient affects dividends with the control variable return on assets with acquisition significance value of 0.047 <0.05.